Study of expression patterns of cytokeratin 8 and 18 in oral cancers - Shaila Kumari Mitra; R. K. Misra; Rajesh Rai; Priyanka Rai; Murari Lal Arya (Tropical Journal of Pathology and Microbiology, 2016)
Introduction: Squamous cell carcinoma of oral cavity is a morphological heterogenous disease. Cytokeratin (CK) comprises a diverse group of intermediate filament protein that are expressed as pairs in both keratinized and non keratinized epithelial tissue. Very little is known of CK alteration in oral intraepithelial neoplasia III (OIN III) and invasive squamous cell carcinoma (SCC).The aim of the study is to evaluate the expression pattern of CK8/18 in oral carcinoma and to establish any correlation between the expressions of CK8/18 with tumor differentiation.Material and Methods: A total of 104 cases of Paraffin embedded formalin fixed sections from oral squamous cell carcinomas (N=60) including benign and inflammatory lesions (control;N=40) and oral intraepithethelial lesions(N=4) were stained with Haematoxylin and eosin stain and and then studied immunohistochemically using CK8 and CK18 immunomarkers.Result: Out of 60 cases of invasive squamous carcinomas, cytokeratin 8 showed positivity in 34 cases (56.67%) while expression of cytokeratin 18 was observed in 25 cases(41.67%) but its expression were absent in control and oral intraepithelial cases. Expression of CK 8 was seen in majority of poorly differentiated 4/5(80%) followed by moderately differentiated 12/17(70.59%), with its expression were significantly higher (56.67%) in invasive oral carcinomas compared with controls statistically. Similarly CK18 expression was seen in majority of poorly 4/5 (80%) followed by moderately differentiated squamous cell carcinomas 7/17(41.18%).Conclusion: Aberrant expression of CK8/18 could be correlated with differentiation and recurrence and shows a great promise to be used as prognostic marker for human oral cancer.